Textile weaving - primitive and modern - Ballou, Jessie Mary (My University, 1905)
Introduction: “Man in his natural state has few wants to provide for food and clothing being the principal ones; to provide the later in a suitable from is a subject which occupies a considerable portion of time in civilized life. One writer observes that, though we find finery and external adornments common to every people, yet comfortable clothing is almost exclusively confined to the inhabitants of those portions of the globe which are for advanced in civilization.” Man’s first article of clothing seems to have been fig leaves and immediately afterward the skin of beasts. Spinning and weaving were undoubtedly the earliest arts known to man and at the present day they are among those arts which form the main distinction between savage and civilized life. At an early period manufacturers of goats’ hair used the make tents similar to those the Arabs of the present day are in the habit of construction. This fabric is supposed by some to have been spun and woven according to the worsted process, resembling to some extent the manufacture of mohair at the present day as distinguished from the making of woolen or felted goods. The art of weaving is of great antiquity among the Chinese, Windows and Egyptians having been practiced by them for thousands of years. Pliny says the Egyptians were the inventors of weaving; “that they put a shuttle in the hands of their goddess, Isis, to signify that she was the inventress of weaving.”
Citation: Ballou, Jessie Mary. Textile weaving - primitive and modern. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Fabrics of the Early Peoples; Manufacature and Tools; Invention of Loom; Theses